Historical and legal aspects of the implementation of citizens ' rights to land: on the example of the North Kazakhstan region - Teleuyev, Г.Б.; Bekturganov, А.Е.; Bekezhanov, Д.Н. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The purpose of the presented scientific research is to conduct a study of the historical legal aspects of the realization of citizens' rights to land on the example of Northern Kazakhstan. Determination of land use characteristics depending on geographical climatic conditions. Determining the impact of the evolution of land legislation on the indigenous population of Northern Kazakhstan. The study of the issues of legal support of land relations in Northern Kazakhstan will contribute to the development of scientific answers to the questions raised so far regarding the implementation of land rights of the local population. As a result of the research, scientific and theoretical conclusions were made regarding the historical and legal aspects of the realization of citizens' rights to land and the prospects for its development. Understanding the historiography of the state legal regulation of land relations, historical and legal aspects of the realization of citizens' rights to land, the formation of author's views on this issue and the definition of stages of state legal regulation of land relations in the northern region of the Republic of Kazakhstan based on the analysis of historical legal documents; from a historical legal point of view, the legal assessment of the protection of the rights of the population of the northern region of the Republic of Kazakhstan to land should be unified, approaches to identifying and solving issues of the realization of citizens' rights to land in Northern Kazakhstan are proposed. This research is funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. BR24993047)